Facile one-pot synthesis of 3D graphite–SiO2 composite foam for negative resistance devices. Issue 66 (29th August 2017) - Wu, Ye; Fu, Hao; Roy, Amitava; Song, Pengfei; Lin, Yingcheng; Kizilkaya, Orhan; Xu, Jian
Abstract : Facile one-pot synthesis of graphite–SiO2 foam for negative resistance devices. Abstract : In this study, we successfully prepare a porous graphite–SiO2 composite foam via a facile glucose-foaming-based method. The foam was characterized by XRD, XPS, SEM, Raman, and soft X-ray absorption spectroscopy of the carbon and oxygen K-edges and by silicon K-edge X-ray absorption near edge structure (XANES) spectroscopy. The electrical properties of the sample were evaluated using current–voltage measurements. The synthesized graphite–SiO2 composite foam showed negative resistance effect, i.e. an increase in the applied voltage led to a decrease in current. This negative resistance effect can be explained by two possible mechanisms: (1) the existence of defect states and (2) a change in the charge shifting amount.